PERHITUNGAN MEDICAL REIMBURSTMENT PREMIUM DAN DAILY BENEFIT PREMIUM UNTUK SICKNESS INSURANCE - Andini Setyo Anggraeni (Premium Insurance Business Journal, 2022)
The purpose of this study is to calculate premiums for sickness insurance using Helligman Pollard's law of mortality. This research will focus on Medical Reimburstment Premium and Daily Benefit Premiums. Data on the size of claims, z (frequency of claims per individual) and d (duration of claims) where z has a Poisson distribution (0.8) and claims size is lognormally distributed (1,5,1). The premium calculation will be aggregated for 5 years and starting from the age of 15 years to 70 years. The premium for daily benefits is higher than the premium for medical reimbursement for all ages. The lowest premium is premium for 25-30 years old, which is 8.518657957 for medical reimbursement premium and 41.79084811 for daily benefit premium, while the highest premium is for 65-70 years old, which is 114.2254996 for medical reimbursement premium and 258.6346296 for daily benefit premiums. Keywords : Sickness Insurance, Premium, Medical Reimburstment, Daily Benefit